Early- and late-onset preeclampsia and the tissue-specific epigenome of the placenta and newborn. (October 2017) - Herzog, Emilie M.; Eggink, Alex J.; Willemsen, Sten P.; Slieker, Roderick C.; Wijnands, Kim P.J.; Felix, Janine F.; Chen, Jun; Stubbs, Andrew; van der Spek, Peter J.; van Meurs, Joyce B.; Steegers-Theunissen, Régine P.M.
Abstract: Introduction: Preeclampsia (PE) carries increased risks of cardiovascular- and metabolic diseases in mothers and offspring during the life course. While the severe early-onset PE (EOPE) phenotype originates from impaired placentation in early pregnancy, late-onset PE (LOPE) is in particular associated with pre-existing maternal cardiovascular- and metabolic risk factors. We hypothesize that PE is associated with altered epigenetic programming of placental and fetal tissues and that these epigenetic changes might elucidate the increased cardiovascular- and metabolic disease susceptibility in PE offspring. Methods: A nested case-control study was conducted in The Rotterdam Periconceptional Cohort comprising 13 EOPE, 16 LOPE, and three control groups of 36 uncomplicated pregnancies, 27 normotensive fetal growth restricted and 20 normotensive preterm birth (PTB) complicated pregnancies. Placental tissue, newborn umbilical cord white blood cells (UC-WBC) and umbilical vein endothelial cells were collected and DNA methylation of cytosine-guanine dinucleotides was measured by the Illumina HumanMethylation450K BeadChip. An epigenome-wide analysis was performed by using multiple linear regression models. Results: Epigenome-wide tissue-specific analysis between EOPE and PTB controls revealed 5001 mostly hypermethylated differentially methylated positions (DMPs) in UC-WBC and 869 mostly hypomethylated DMPs in placental tissue, situated in or close to genes associated with cardiovascular-metabolic developmental pathways. Discussion: This study shows differential methylation in UC-WBC and placental tissue in EOPE as compared to PTB, identifying DMPs that are associated with cardiovascular system pathways. Future studies should examine these loci and pathways in more detail to elucidate the associations between prenatal PE exposure and the cardiovascular disease risk in offspring. Highlights: Preeclampsia (PE) offspring has been associated with increased risks of cardiovascular disease in adulthood. We found 5001 cord blood and 869 placental differentially methylated positions (DMPs) in EOPE. Our epigenome-wide DMPs match to genes associated with cardiovascular development. These DMPs might elucidate the cardiovascular disease susceptibility in PE offspring.